Pengaruh Integrasi Pembelajaran Mendalam dalam Perencanaan Pembelajaran Bahasa Indonesia terhadap Keterampilan Menulis Murid Kelas X di SMAN 4 Makassar - Nurfadillah; Alsa Putri, Febrianingsih; Safitri, Alya; Riska; Candra Dewi, Anita (STKIP Subang, 2026)
This study aims to determine the level of in-depth learning and writing skills of grade 10 students at SMAN 4 Makassar and examine the relationship between the two variables. The study used a quantitative approach with a correlational method on 31 students through a total sampling technique. Data were collected using a four-point Likert scale questionnaire and analyzed using descriptive statistics and the Pearson Product Moment correlation test. The results showed that in-depth learning was in the high category with an average of 36.7, while writing skills were also in the high category with an average of 35.1. The results of the correlation test showed a correlation coefficient (r) of 0.55, which means there is a positive relationship with the medium category, so that higher in-depth learning tends to be followed by an increase in writing skills, although the relationship is not very strong. Thus, in-depth learning contributes to students' writing skills, but other supporting factors such as writing practice and continuous learning strategies are still needed to achieve optimal results.